Geoenvironmental Engineering 2014
DOI: 10.1061/9780784413432.017
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Soils and Soil Lime Mixtures As Liners to Retain Heavy Metal Ions in Aqueous Solutions

Abstract: In this study, the relative performance of two soils after amending them with suitable matrices, in retaining the heavy metal ions has been evaluated. Al-Ghat soil and Al-Qatif soil of Saudi Arabia were mixed with different percentages of lime. Heavy metal ions such as copper and chromium were used to carry out sorption studies. Experimental data was used to plot adsorption isotherms. Langmuir isotherm was found to be more suitable than Freundlich isotherm for all soil mixtures. It can be concluded that Al-Qat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In order to study the desorption response, leaching tests were conducted in accordance with ASTM -D3987 [24] maintaining load ratios of 100mg/kg and 50 mg/kg for both copper and chromium metal ions. This load ratio is consistent and it is not expected to influence any major change in leaching rate [1]. It can be observed from Fig.…”
Section: Leaching Testssupporting
confidence: 60%
See 2 more Smart Citations
“…In order to study the desorption response, leaching tests were conducted in accordance with ASTM -D3987 [24] maintaining load ratios of 100mg/kg and 50 mg/kg for both copper and chromium metal ions. This load ratio is consistent and it is not expected to influence any major change in leaching rate [1]. It can be observed from Fig.…”
Section: Leaching Testssupporting
confidence: 60%
“…Maximum adsorption takes place at acidic pH and due to protonation (defined as the attachment of H + ions forming complexes in acidic media). If the concentration of H + ions is more it would lead to better protonation [1,25]. From Fig.…”
Section: Leaching Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…This increased the efficacy of NCS as a stabilizing material for long-term attenuation requirements of the industry. Further, to validate the use of NCS as a soil amendment, many more leaching tests have been performed under various conditions [17,18,21]. It was found that because of the organic nature of BCS and being an expansive soil with low strength parameters, it was decided to continue further tests only with red soil.…”
Section: Results and Discussion Leaching Studiesmentioning
confidence: 99%
“…Also, the longterm effects of this mixture is worthy of investments as this gives a permanent solution. This method uses only existing moisture in soil; however, cement-based solidification occurs slowly and requires excess of water to solidify while additional treatment costs are involved for gene rating secondary effluents from cement-based S/S techniques [17,29].…”
Section: Mechanism Of Encapsulation and Economic Analysismentioning
confidence: 99%